2020
DOI: 10.1080/13467581.2020.1726763
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of CO2 emission reduction effect using in-situ production of precast concrete components

Abstract: Precast concrete (PC) construction method is typically preferred due to its reduced construction time, quality assurance, and cost effectiveness. Experimental studies have proven that insitu production of PC components ensures equivalent or enhanced quality with substantial cost reductions compared to those of in-plant production, under the same production conditions. The construction method may also be environment friendly due to its relatively low CO 2 emissions. However, it is necessary to examine the degre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…According to an interview with a PC factory official, it was confirmed that if the factory owner does not obtain more than 20% of the production cost as a profit, the official does not contract, because this does not cover the factory management overhead [17]. Through several studies, it has been possible to secure the quality and economic feasibility of in-situ production [14][15][16][17]19]. This study examined in-situ production at a construction site that complied with the PC production and installation guidelines of the KCI (Korea Concrete Institute); it was confirmed that there were no problems with cracks, breakages, size, or strength quality standards.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…According to an interview with a PC factory official, it was confirmed that if the factory owner does not obtain more than 20% of the production cost as a profit, the official does not contract, because this does not cover the factory management overhead [17]. Through several studies, it has been possible to secure the quality and economic feasibility of in-situ production [14][15][16][17]19]. This study examined in-situ production at a construction site that complied with the PC production and installation guidelines of the KCI (Korea Concrete Institute); it was confirmed that there were no problems with cracks, breakages, size, or strength quality standards.…”
Section: Discussionmentioning
confidence: 99%
“…Kim and Chae presented that a considerable amount of CO 2 is emitted during the steam curing stage when making PCs, and proposed a method of evaluating CO 2 emissions throughout the PC life cycle using life cycle assessment [28]. Lim et al calculated CO 2 emissions with the LCA method through an experimental study of in-situ production and determined that the amount of CO 2 emission reduction increases as the quantity of in-situ production increases [19]. These studies were reviewed from the eco-friendly perspective for field application through optimization and evaluation methods for the existing PC method's CO 2 emissions.…”
Section: Preliminary Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Most of these large buildings are built using the precast concrete (PC) method. However, in general, PC methods are produced in factories and transported to the site [8]. In order to reduce CO 2 emissions generated in this process, the on-site production of PC members is essential.…”
Section: Introductionmentioning
confidence: 99%